Peroxiredoxin V Inhibits Emodin-induced Gastric Cancer Cell Apoptosis via the ROS/Bcl2 Pathway - JIN, YONG-ZHE (In Vivo, 2019)
Background/Aim: Peroxiredoxin (Prx) protein family is aberrantly expressed in various cancers including gastric cancer. Among the six family members, Prx V has been known as an antioxidant enzyme which scavenges intracellular reactive oxygen species (ROS) and modulates cellular apoptosis. This study aimed at investigating the role of Prx V in apoptosis of gastric cancer cells. Materials and Methods: Stably constructed Prx V knockdown, over-expression and mock AGS cells (a human gastric adenocarcinoma cell line) were used to study the effect of Prx V on emodin-induced apoptosis by western blotting, cell viability, apoptosis and ROS detection assays. Results: Overexpression of Prx V significantly decreased emodin-induced cellular apoptosis and ROS levels compared to Mock and Prx V knockdown AGS cells. Also, overexpression of Prx V down-regulated the expression of pro-apoptotic proteins, Bad and cleaved PARP, and increased the expression of anti-apoptotic protein, Bcl2. Conclusion: Prx V suppresses AGS cell apoptosis via scavenging intracellular ROS and modulating apoptosis-related markers.